HUBUNGAN TINGKAT STRES DENGAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI TENGAH PANDEMI COVID-19 DI PUSKESMAS CIPUTAT - Ummi Nurahmah (2021)
In the early year 2020, the woeld is fueled by the discovery of a new virus, a new kind of Corona Virus (sars-cov-2) and known as the Corona Virus Disease 19 (COVID-19). The covid-19 case is a high-health concern both in the world and in Indonesia. To cope with covid-19's disease by applying proper and consistent health protocols, the elderly of this pandemik is a source of great stress because of the concern infected with this virus and diminished family income. The study is aimed at finding out the incidence of stress with blood pressure on hypertensive people in hypertension amid hypertension in the affected central areputation center. The method used was chi square. The data retrieval uses a total sampling and a total sample of 50 respondents. The data analysis used isa univariate and bivariate analysis with the chi square test and enhanced with spearmen test. The results of this chi square test show the presence of stress levels with blood pressure with positive direction and enough power. Keywords: covid-19, elderly, stress, hypertension